PERLINDUNGAN HUKUM TENAGA HONORER SETELAH BERLAKUNYA UNDANG-UNDANG NOMOR 5 TAHUN 2014 TENTANG APARATUR SIPIL NEGARA - Made Aditya Pramana Putra (University of Udayana, 2016)
The emergence of The State Civil Apparatus (No. 5 of 2014) gives an impact to position and the legal protection to honorary employees. According to that law, honorary employee was substituted by the government employee with treaty of work. This substitution makes the honorary employees do not have status and legal protection. The aim of this study is to examine position and legal protection of the honorary employee. This study used normative, legislation, historical, and conceptual approaches. Legal materials used in this study come from primary, secondary, and tertiary, which used library research methods. This study found that since the government publishes the Law No. 5 of 2014 to substitute the Law no. 43 of 1999, the status and the legal protection of the honoraryemployee became unclear. This is because of the government was not able to handle the problem of the honorary employee, especially for the salary, recruitment, and the status. However, actually the case is honorary employee have been playing important roles in government institution. Thus, the Law of the State Civil Apparatus should makes a better protection for the government employee with treaty work as a substitute for the honorary employee. Terbitnya Undang-Undang nomor 5 tahun 2014 tentang Aparatur Sipil Negarasangat mempengaruhi kedudukan dan perlindungan hukum bagi tenaga honorer.Dalam undang-undang tersebut, istilah tenaga honorer diganti menjadi pegawai pemerintah dengan perjanjian kerja. Penelitian ini bertujuan untuk mengkaji posisi dan perlindungan hukum bagi tenaga honorer. Penelitian ini menggunakan pendekatan normatif, perundangan, historis, dan konseptual. Materi hukum yang digunakan dalam penelitian ini berasal dari sumber primer, sekunderm dan tersier, dengan menggunakan metode studi pustaka. Penelitian ini menemukan bahw sejak diterbitkannya Undang-undang No. 5 Tahun 2014 yang menggantikan Undang-Undang No. 43 Tahun 1999, status dan perlindungan hukum tenaga honorer menjadi tidak jelas. Hal ini disebabkan karena pemerintah tidak mampu mengatasi permasalahan tenaga honorer, terutama yang berkaitan dengan sistem penggajian, rekrutmen, dan kejelasan status. Padahal, tenaga honorer mempunyai peran penting dalam institusi pemerintahan. Dengan demikian, Undang-undang Aparatur Sipil Negara seharusnya mampu memberikan perlindungan yang lebih baik bagi pegawai pemerintah dengan perjanjian kerja sebagai pengganti tenaga honorer.